“My” David Lodge: Recollections Punctuated by Coincidences - Mullini, Roberta (Linguæ & - Journal of Modern Languages and Cultures, 2025)
On the occasion of David Lodge’s death, in this invited short memoir Roberta Mullini, former professor of English literature at the University of Urbino, traces the history of her personal literary relationship with David Lodge through reading, teaching and writing about his novels. An appendix with comments about Lodge by some former students of hers concludes the article.